Web-Based Diniyah Teacher Salary Distribution Information System at the Banda Aceh City Education and Culture Office - Rizaldi, Rahmad (International Journal Education and Computer Studies (IJECS), 2021)
The objectives of the research conducted include; 1) Develop a Salary Distribution Information System to be applied in the process of disbursing the salary of diniyah teachers, 2) Develop a website application that can assist treasurers in the process of distributing salaries appropriately, and 3) Develop a website-based salary assignment application that can make it easier for treasurers to make salary transfer reports. . To obtain data as material for writing research and discussing problems, the authors use the method of observation, interviews, literature review, and design analysis, while in application development using the waterfall method. From the results of research and observations that have been carried out at the Education and Culture Office of Banda Aceh City, the following conclusions can be drawn; 1) With the web-based information system on the distribution of diniyah teachers' salaries at the Banda Aceh City Education and Culture Office and the work on making payroll is precise, and accurate, especially in the personnel department, and getting information about the teacher's salary becomes easier 2) Information system This is able to overcome the problems that often occur at the Education and Culture Office of Banda Aceh City, namely it is difficult to control and supervise employee data and salary preparation which can avoid delays and in making employee salary reports every year and a certain period, and 3) The creation of an information system program in order to obtain quality information.